Kamishibai in kindergarten: The magic of ancient Japanese storytelling with young learners - Ansaldo, Matías (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
The art of Kamishibai also known as paper drama has been treasured by Japanese storytellers. As part of the annual multicultural school year in Argentina, EFL kinder teachers held a project to provide students with vivid, holistic and enriching experiences related to this ancient tradition. Students, whose native language is Spanish, were immersed in the Far eastern culture and literature in English. Could teachers involve students in the magical world of ancient Japan? How would they do it? Yoga sessions, tea ceremony and stories retold with the art of Kamishibai. After listening to many stories, students were ready to create their own in groups with the help of the teachers. Those stories were carefully prepared, illustrated and then narrated to other students and parents, following the art of the Kamishibai.